(untitled) (International Journal of Engineering and Computer Science, 2015)
Wireless Sensor Networks (WSN) is an emerging technology in today’s world. A WSN consist of thousands of sensor nodes it will perform sensing, computation and communication. Most of the sensor nodes are powered by batteries so there is a need of an energy efficient routing scheme in WSN. Many cluster based routing algorithms have been developed based on energy efficiency. In this paper, we propose a power aware cluster based routing with sleep scheduling in WSN for prolonging the sensor network lifetime. Here Cluster Head(CH) is selected based on number of neighboring nodes and the remaining residual energy of sensor node. In order to prolong network lifetime we are also using Sleep Scheduling in WSN. Most of the nodes are kept to sleep state to conserve energy and sleep scheduling will increase network lifespan. Evaluation of the system is done with Network Simulator-2 (NS-2). We are also comparing proposed system with system without sleep scheduling. The simulation results shows that the proposed approach prolongs the network lifetime and balancing the energy consumption among the nodes of the cluster.